1976
DOI: 10.1029/jc081i012p01960
|View full text |Cite
|
Sign up to set email alerts
|

On polarization features of radio signals scattered from the sea surface at small grazing angles

Abstract: Measured results are presented of the amplitude and spectral characteristics of the envelopes of vertically and horizontally polarized and cross-polarized 3.2-cm radar backscatter signals from the surface of the sea at grazing angles • < 8 ø with fine range resolution. The features of scattering on vertical polarization are explained completely by the 'two-scale' modele For horizontal polarization, relatively stable backscatter signals, called 'bursts,' are observed in addition to the signals scattered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 7 publications
0
43
0
1
Order By: Relevance
“…His observation, reported in volume 13 of the MIT Radiation Laboratory Series, is probably the earliest documentation of superevents observed in microwave backscatter. From the mid-1960s to the mid-1970s, Pidgeon [1968] documented the separation of VV and HH Doppler peaks; Mel'nichuk and Chernikov [1971] noted the failure of the Bragg scattering mechanism to explain small grazing angle backscatter; Long [1974] correlated return spikes with wave breaking; Leykin et al [1975] noted that at small grazing angles, the horizontal polarization returns are mainly due to backscatter from the crest region of larger waves and stated that breaking wave crests contributed significantly to the horizontal returns; and Kalmykov and Pustovoytenko [1976] documented the observation of spiking and superevents. In 1991, Jessup et al [1991] observed superevents but tentatively attributed the signals to wedge scattering, "random fluctuations in the measurements or the effects also the dominant non-Bragg scattering mechanism for fast scatterers at small grazing angles.…”
Section: Introductionmentioning
confidence: 99%
“…His observation, reported in volume 13 of the MIT Radiation Laboratory Series, is probably the earliest documentation of superevents observed in microwave backscatter. From the mid-1960s to the mid-1970s, Pidgeon [1968] documented the separation of VV and HH Doppler peaks; Mel'nichuk and Chernikov [1971] noted the failure of the Bragg scattering mechanism to explain small grazing angle backscatter; Long [1974] correlated return spikes with wave breaking; Leykin et al [1975] noted that at small grazing angles, the horizontal polarization returns are mainly due to backscatter from the crest region of larger waves and stated that breaking wave crests contributed significantly to the horizontal returns; and Kalmykov and Pustovoytenko [1976] documented the observation of spiking and superevents. In 1991, Jessup et al [1991] observed superevents but tentatively attributed the signals to wedge scattering, "random fluctuations in the measurements or the effects also the dominant non-Bragg scattering mechanism for fast scatterers at small grazing angles.…”
Section: Introductionmentioning
confidence: 99%
“…Field observations of low-grazing angle backscatter and its potential relation to wave breaking date back over 30 years [see Pidgeon, 1968;Kalmykov and Pustovoytenko, 1976;Trizna, 1991]. Many observations have focused on characterizing the amplitude distribution of sea clutter for the purpose of rejecting it in surveillance radar applications.…”
Section: Introductionmentioning
confidence: 99%
“…According to the photographs and data taken in the field experiments [14,24], the single sharply crested unbroken wave can be approximately simulated with the dihedral wedge of finite length shown in Figure 1. Different from the infinite two-dimensional wedge in the previous literatures, the dihedral wedge is characterized by internal angle β, length d, width 2l and height h. Since the size of the wave crest is related to incidence microwave, d and 2l are presented in wavelength of incidence wave λ.…”
Section: Wedge-like Breaking Wavementioning
confidence: 99%
“…According to the measured data and the photographs of the sea surface at LGA, Kalmykov and Pustovoytenko assumed that the wedges could approximate the sharp crests, which led to the increase of polarization ratio (HH/V V ) [24]. Kwoh and Lake also suggested that the dominant scattering from the wave crest could be approximated by wedge scattering and analyzed the relationship of scattering fields from capillary wave and the wedge-shaped crest with small perturbation method (SPM) and geometrical theory of diffraction (GTD) respectively [25].…”
Section: Introductionmentioning
confidence: 99%